2020
DOI: 10.3389/fendo.2020.00185
|View full text |Cite
|
Sign up to set email alerts
|

Combating Obesity With Thermogenic Fat: Current Challenges and Advancements

Abstract: Brown fat and beige fat are known as thermogenic fat due to their contribution to non-shivering thermogenesis in mammals following cold stimulation. Beige fat is unique due to its origin and its development in white fat. Subsequently, both brown fat and beige fat have become viable targets to combat obesity. Over the last few decades, most therapeutic strategies have been focused on the canonical pathway of thermogenic fat activation via the β3-adrenergic receptor (AR). Notwithstanding, administering β3-AR ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 120 publications
2
46
0
Order By: Relevance
“…It was demonstrated that scWAT exhibits a greater potential than VAT to undergo beiging, a process by which white adipocytes become brown-like and participate in energy dissipation ( 2 , 347 ). Indeed, the induction of VAT beiging has been largely regarded as an approach to curb obesity and its accompanying metabolic and cardiovascular derangements ( 348 , 349 ). Nevertheless, several visceral adipose depots including PVAT and EpiCAT intrinsically possess a beige phenotype and the implications of thermogenic induction in these particular tissues on cardiovascular functioning is not yet well-characterized, especially that the immune landscape of these tissues is less known ( 33 ).…”
Section: Immune Cell Contribution To Depot-specific Adipose Tissue Inmentioning
confidence: 99%
“…It was demonstrated that scWAT exhibits a greater potential than VAT to undergo beiging, a process by which white adipocytes become brown-like and participate in energy dissipation ( 2 , 347 ). Indeed, the induction of VAT beiging has been largely regarded as an approach to curb obesity and its accompanying metabolic and cardiovascular derangements ( 348 , 349 ). Nevertheless, several visceral adipose depots including PVAT and EpiCAT intrinsically possess a beige phenotype and the implications of thermogenic induction in these particular tissues on cardiovascular functioning is not yet well-characterized, especially that the immune landscape of these tissues is less known ( 33 ).…”
Section: Immune Cell Contribution To Depot-specific Adipose Tissue Inmentioning
confidence: 99%
“…In the case that beige fat exists in WAT contributing to energy consumption (12), it is promising to induce beige fat development in WAT. Notably, in recent years, studies using rodent models have shown a high plasticity of beige adipocytes regarding to its origin and regulation, the results of which have been summarized in our latest review article (71). Unlike BAT, the origin of murine beige adipocytes reported so far could be white adipocyte via transdifferentiation or distinct progenitors including PDGFRα + , mural, or MyoD + progenitors via differentiation (72)(73)(74)(75)(76)(77).…”
Section: Prospects From Rodent Experiments To a Better Metabolic Healmentioning
confidence: 99%
“…Beiging, either through CE or β3AR agonists, has been linked to metabolic improvements, namely through increased glucose tolerance and insulin sensitivity (Baskin et al, 2018; Carpentier et al, 2018; Chen et al, 2020; Cypess et al, 2015; Darcy & Tseng, 2019; Finlin et al, 2018; Hao et al, 2019; Herz & Kiefer, 2019; Jiang et al, 2017; Loh et al, 2019; Marlatt & Ravussin, 2017; O’Mara et al, 2020; Pan et al, 2020; Peres Valgas da Silva et al, 2019; Phillips, 2019; Singh et al, 2020; Srivastava & Veech, 2019; Wang et al, 2019). Activation of the β3AR by NE on BAT initiates a cascade of secondary messengers within the cell.…”
Section: Introductionmentioning
confidence: 99%
“…Many compounds ranging from naturally occurring antioxidants to hormones, to various β3AR agonists have been investigated. The most promising results are found with β3AR agonists, although many of them are accompanied by undesirable cardiovascular side effects (Baskin et al, 2018; Carpentier et al, 2018; Chen et al, 2020; Cypess et al, 2015; Finlin et al, 2018; Hao et al, 2019; Herz & Kiefer, 2019; Loh et al, 2019; Marlatt & Ravussin, 2017; O’Mara et al, 2020; Pan et al, 2020; Pouleur et al, 2018; Singh et al, 2020). β3AR agonists and their possible use in combating metabolic disorders has previously been discussed elsewhere (Chen et al, 2020; Cypess et al, 2015; Marlatt & Ravussin, 2017; Michel et al, 2010; Schena & Caplan, 2019).…”
Section: Introductionmentioning
confidence: 99%